Mixed farming systems in sub-Saharan Africa - Mohamed-Saleem, M.A. (Food and Agriculture Organization of the United Nations, 1995)
The important position and role of mixed farming systems in land use intensification in subSaharan Africa is reviewed. This is done by examining the current situation that is followed with a justification for mixed farming. Further sections follow on changing patterns of land use, including the effects of tsetse flies and trypanosomiasis, and on constraints to further crop-livestock integration. Research needs are considered in a final section with particular emphasis on biophysical factors (feed development, nutrient management, dualpurpose livestock, animal health, genetic improvement and natural resource management) and policy analysis.